THE EFFECT OF PROFITABILITY ON COMPANY VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLES - Barna, Rafly Tyas; Pertiwi, Tri Kartika (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
The objective of this study is to determine the effect of profitability on firm value with dividend policy as a mediating variable of manufacturing companies from 2016-2019. This study is quantitative research. The applied population is 62 companies, and samples are 17 companies. The profitability proxied by the ROA, the firm value proxied by the PBV, and the dividend policy proxied by the DPR. The result of the analysis shows that profitability has a significant positive effect on firm value. Profitability has a positive and significant effect on dividend policy. Dividend policy has a negative and not significant effect on firm value. The dividend policy is not significant as mediates the effect of profitability on firm value in manufacturing companies.